PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY BERBANTUAN MEDIA KOTAK KARTU MISTERI UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS X SMA IT BANGKINANG - Wardhani S., Ayu Nabila; Isjoni; Asril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ interest in learning history through the implementation of the Two Stay Two Stray (TSTS) cooperative learning model assisted by Mystery Card Box media in Grade X of SMA IT Bangkinang. This research is motivated by the low level of students’ learning interest, which is indicated by a lack of attention, low participation, and the perception that history is a monotonous subject. The research method employed was Classroom Action Research (CAR) using the Kurt Lewin model, consisting of two cycles that included planning, action, observation, and reflection stages. The research subjects were Grade X students of SMA IT Bangkinang. Data were collected through observations of teacher and student activities and a learning interest questionnaire. The results showed an improvement in the learning process and students’ interest after the implementation of the Two Stay Two Stray model assisted by the Mystery Card Box media. The average percentage of students’ learning interest in Cycle I was 47%, categorized as low, and increased to 55% in Cycle II, categorized as moderate. This improvement indicates a positive change in students’ engagement and motivation during history learning activities. Therefore, it can be concluded that the Two Stay Two Stray cooperative learning model assisted by Mystery Card Box media is effective in increasing students’ interest in learning history in Grade X of SMA IT Bangkinang.